Para uma caracterização da distinção entre palavras prosódicas e clíticos com base em dados de frequência - Vigário, Marina (2017)
The frequency of various phonological patterns in prosodic words (PW) and phonological clitics (CL) was systematically inspected in a corpus of European Portuguese containing ca. half a million words. Clear differences were found between the two types of words in the use of the segmental inventory of the language (in stressless position), in the frequency of individual segments, in syllable types, in the (proportion of) allowed word shapes, and in the token/type distribution, a.o.. Given the known ability of infants to process statistical patterns in the language input, it is proposed that the frequency of phonological patterns should be added to the set of aspects that may play a role in the acquisition of the distinction between PWs and CLs, which in turn can be seen as a precursor of the distinction between lexical and function words.